PENGEMBANGAN E-MODUL DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Zakiyatul Miskiyyah, Zakiyatul Miskiyyah; Achmad Buchori (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
This research aims to find out the validity of e-modules using Culturally Responsive Learning approach on the material of two variable linear equation systems. The research method used is research and development. This research use the development model ADDIE (Analysis, Design, Development, Implementation, Evaluation) however the researcher only conducted the research until the stage of Development due to the time limit in the manufacture of products and their validation. E-modul using Culturally Responsive Learning is validated by material expert and media expert. The result of the research shows that, the average assessment of material expert validation was obtained 93%, while validation of media expert 96%. Thus e-modules with a culturally responsive learning approach are well worth using.